2009
DOI: 10.1007/s12562-009-0099-8
|View full text |Cite
|
Sign up to set email alerts
|

Repeatable immersion infection with Photobacterium damselae subsp. piscicida reproducing clinical signs and moderate mortality

Abstract: Pseudotuberculosis is a bacterial septicaemia caused by Photobacterium damselae subsp. piscicida in several marine fish species. Yellowtail Seriola quinqueradiata is the most sensitive fish species to this disease. The internal organs of naturally infected yellowtail exhibit whitish spots, tubercle-like tissue structures, consisting of bacterial accumulations. There have been many trials for experimental infection, however adequate method of infection that reproduces moderate mortality and primary clinical sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The natural route of infection for P. damselae subsp. piscicida is unknown to date (Nagano, Inoue & Kawai 2009). In the present study, i.p.…”
Section: Discussionmentioning
confidence: 99%
“…The natural route of infection for P. damselae subsp. piscicida is unknown to date (Nagano, Inoue & Kawai 2009). In the present study, i.p.…”
Section: Discussionmentioning
confidence: 99%
“…All fish dead during the challenge showed high bacterial load in the three tissues analysed (i.e., spleen, liver and gills) with spleen consistently showing higher levels of bacterial colonization than gills and liver. Recently, the early process of Phdp infection was investigated in Seriola quinqueradiata by immersion challenge (Nagano, Inoue, Kawai, & Oshima, ). This study clearly indicated the gills as the site of election to initiate infection, while internal organs (spleen, kidney) appeared to be the final tissues where bacterial proliferation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The culture titre was determined in 100 μL of the bacterial suspension by preparing serial dilutions in tubes containing 900 μL of culture medium, transferring 100 μL and plating. An OD630 nm∼0.9 of the initial culture corresponded to approximately 10 9 bacteria cells/mL [61] . Artemia metanauplii that received no pathogen served as control and survival was monitored throughout the experiment (24–144 h).…”
Section: Methodsmentioning
confidence: 99%